Dysfunkcjonalność rodziny a dysfunkcjonalność władzy rodzicielskiej - Jakimiec, Daniel (Biuletyn Historii Wychowania, 2019)
The family represents a fundamental social unit, consisting of individuals connected by marital and parental bonds. The relations between family members are determined by traditions handed down by means of upbringing, which, in turn, is based on shared emotions and attitudes subjected to the laws and moral order of nature. The prerogatives recognised by the family are also heavily affected by religious axioms. Generally speaking, the family represents the cultural legacy of whole generations falling under the influence of numerous factors, each of them being a link in the family’s history. The analysis of the function of the family as a fundamental social group and of parental responsibility indicates that the functions of the family are more extensive than the functions of parental responsibility. This is because the functions of the family are fulfilled by all its members, adults and minors alike. Those functions performed by adult family members are subject to a number of norms included in the Family and Guardianship Code. However, the family’s desired performance positively affects fulfilment of parental responsibility.